E-books: emergent reality - Cordón-García, José-Antonio (Anuario ThinkEPI, 2010)
After years of failures and hesitations, electronic books have consolidated their market presence, representing an increasingly important segment of the publishing sector. This launch is due to several factors: implementation of the electronic edition as an inseparable part of content production, primarily in science and reference works; technological improvements, advantages, and greater variety in reading devices; an increasingly large and diverse catalog of works developed by publishers of all kinds; and the responsiveness to new media demonstrated by the reading public. Despite this, there are several problems, mainly related to format and to management of electronic rights, that the industry must resolve to ensure that this trend will continue permanently.